(untitled) (Proceedings of Southern Federal University. Philology, 2019)
Olga B. Bobrova (Moscow, Russian Federation) The contemporary theory considers the conventional metaphor as a lexical stereotype fixed in dictionaries and automatically detected and reproduced in speech. While reflecting the interaction of two sustainable cognitive spheres this stereotype is directly linked with the conceptual system of a person and their linguistic world image. The system of conventional metaphors of the Russian language is described in detail in a number of scientific papers. At the same time, the prospects for utilising the conventional metaphor theory in the study of other languages, as well as in the study of original texts remain unclear. In order to answer both questions, the present article considers the conventional metaphors used in Nikos Kazantzakis’s “Ταξιδεύοντας” travelogue. The metaphors are analysed both in terms of semantics (qualitatively) and in terms of prevalence in the text (quantitatively). The analysis shows the promising use of the conventional metaphor theory based on the material of the modern Greek language, while revealing certain peculiarities of studying conventional metaphors in original texts. Key words: New Greek literature, Nikos Kazantzakis, language metaphor, conventional metaphor, «Ταξιδεύοντας». DOI 10.23683/1995-0640-2019-3-69-79